The contributions of teacher intercultural competence to academic satisfaction and engagement among international students in China and Thailand - Guo, Linzhi; Laokulrach, Marisa (Nurture, 2023)
Purpose: The contributions of teacher intercultural competence to educational outcomes, including student self-efficacy, engagement, and academic satisfaction, were investigated in this study. Design/Methodology/Approach: The study applies the quantitative method using primary data from the survey collected from 400 international undergraduate students in China and Thailand. The partial least squares structural equation modeling is used to analyze the relationships of variables between conceptual constructions. Findings: The results indicate that teacher intercultural competence has positive and significant effects on international student self-efficacy and engagement but has no significant effect on international student academic satisfaction. Conclusion: This study provides new insight into international student self-efficacy, engagement, and academic satisfaction from the perspective of teacher intercultural competence. Research Limitations/Implications: In this study, undergraduate international students were selected only from China and Thailand, which is considered a research limitation. Thus, increasing the generalizability of the whole population by collecting data from more universities is suggested for future research. Practical Implications: Educational policymakers or university administrators should improve international student educational outcomes from the perspective of teacher education and professional development. Teacher intercultural competence should be considered a significant part of teacher education and professional development. If the teachers understand the cultural or behavioral differences from the perspective of students, they can construct a more inclusive and effective academic environment. Contribution to Literature: This study proposed and confirmed the mediating role of international student self-efficacy, which brings clarification to the formational mechanism of how teacher intercultural competence affects international student engagement and academic satisfaction.